PENERJEMAHAN INGGRIS-ARAB NAMA ALIRAN POLITIK: STUDI KASUS PADA MAUSŪ’AH AS-SIYĀSAH KARYA ABDUL-WAHHAB AL-KAYYALIY - Hamdan Hamdan (Arabic Literature Department, 2018)
This article aims to discuss the Arabic translation of the names of English political doctrines by focusing on Mausū’ah as-Siyāsah written by ‘Abdul-Wahhab alKayyaliy. This research was conducted in three steps, namely data collection, analysis, and presentation of results. The source of this research data is literature data that is the names of political doctrines which was translated to Arabic in Mausū’ah as-Siyāsah. The names are recorded on the data card with certain marks and are classified to obtain terminology that clearly describes the process of its formation. In the next step, the terminologies chosen as a sample are analyzed using the theory of semantic fields. The study shows that the Arabic translation for the names of the political doctrines has two types, namely the Arabization (taʻrīb) and using the equivalent of Arabic. Besides, the translation itsels was conducted through a hermeneutical process in which the translation as much as possible took a high accordance with original English text.